2012
DOI: 10.1186/1750-1172-7-65
|View full text |Cite
|
Sign up to set email alerts
|

Assisted reproductive techniques and the risk of anorectal malformations: a German case-control study

Abstract: BackgroundThe use of assisted reproductive techniques (ART) for treatment of infertility is increasing rapidly worldwide. However, various health effects have been reported including a higher risk of congenital malformations. Therefore, we assessed the risk of anorectal malformations (ARM) after in-vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI).MethodsData of the German Network for Congenital Uro-REctal malformations (CURE-Net) were compared to nationwide data of the German IVF register … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 39 publications
4
19
2
1
Order By: Relevance
“…22 However, because we used a limited group of conditions, our prevalence estimates of 1% are lower than national estimates for all types of birth defects (approximately 3%). 27 In accordance with other studies, 35,7,2832 we found that the risk of birth defects following ART varied by type of defect; the largest relative risks were observed for gastrointestinal and limb reduction defects. We also found an association between ART use and transposition of great vessels, which has been previously reported.…”
Section: Discussionsupporting
confidence: 87%
“…22 However, because we used a limited group of conditions, our prevalence estimates of 1% are lower than national estimates for all types of birth defects (approximately 3%). 27 In accordance with other studies, 35,7,2832 we found that the risk of birth defects following ART varied by type of defect; the largest relative risks were observed for gastrointestinal and limb reduction defects. We also found an association between ART use and transposition of great vessels, which has been previously reported.…”
Section: Discussionsupporting
confidence: 87%
“…Candidate genes were also selected based on the knowledge from animal studies, syndromic forms of ARM, or other congenital malformations of the colon. After screening the caudal type homeobox 1 ( CDX1 ) gene, four heterozygous mutations (c.213–214InsGAA, c.6G>C, c.27G>T, c.18A>C) were identified, and lower CDX1 expression levels were found in cases when compared with controls (Zhang et al, ). Although the ret proto‐oncogene ( RET ) is a major gene involved in Hirschsprung's disease, it was not associated with ARM (Wu et al, ).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…In three studies, associations were investigated between ARM and common methods of contraception, including oral contraceptives, spermicides, male condoms, and intrauterine devices; however, no associations were found (Table ; Stoll et al, ; Gallaway et al, ; Waller et al, ). However, assisted reproduction seems to attribute to the occurrence of ARM in several studies, showing highly increased risk estimates ranging from 2.4 to 13.3 (Robert and Francannet, ; Källén et al, ; Midrio et al, ; Reefhuis et al, ; Zwink et al, ). The highest risks were observed in studies comparing personal interviews among case parents with register‐based control data (Midrio et al, ; Zwink et al, ).…”
Section: Nongenetic Factorsmentioning
confidence: 99%
“…However, analysis of data from 2001-2007 by the same group found only oesophageal atresia to be significantly increased. A German study however, noted an increased risk of anorectal malformation with assisted reproduction [8]. A review of the literature does not suggest that malrotation has been identified as being more prevalent in babies conceived via assisted reproductive techniques.…”
Section: Discussionmentioning
confidence: 94%